Histological analysis of low dose NMU effects in the rat mammary gland. - Murray, Tessa J.; Ucci, Angelo A.; Maffini, Maricel V.; Sonnenschein, Carlos.; Soto, Ana M. (2016)
Background: Our objective was to assess the histological changes in mammary glands of the female Wistar-Furth rat as a result of low dose exposure to N-nitrosomethylurea (NMU).; Springer Open.